THE FUNCTION OF INTERNAL AUDIT AND FINANCIAL REPORTING QUALITY: THE MODERATING ROLE OF THE RISK MANAGEMENT COMMITTEE - Yulianti Raharjo; Oryza Tannar; Yani Permatasari (Jurnal Bisnis dan Akuntansi, 2026)
Abstract: This study aims to analyze the moderating role of the risk management committee on the relationship between the internal audit function and the quality of financial reporting. Based on the ordinary least square test results on 715 non-financial companies listed on the Indonesia Stock Exchange in the 2018-2024 period, several test results were obtained. The results show that the existence of an internal audit function in a company can improve the quality of financial reporting. In addition, the existence of a risk management committee can strengthen the relationship between the internal audit function and the quality of financial reporting. Academically, the results of this study are expected to contribute to the literature regarding what factors can improve the quality of corporate financial reporting. Meanwhile, regulators and company management can use the results of this study as consideration for companies to have internal audit functions and risk management committees within their companies as part of the corporate governance mechanism, so that companies can present high-quality financial reporting.